PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PERKEMBANGAN EMOTIONAL INTELLIGENCE (EQ) SISWA KELAS XI DI MA NEGERI 2 SAMARINDA - Nesya Maylafayza Indriani; Dwi Nugroho Hidayanto; Nuril Hidayanti; Rury Muslifar; Syarifudin (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Emotional problems among students can significantly hinder their social and academic growth, emphasizing the need to foster emotional intelligence during adolescence. This study investigates the low ability of students to recognize and regulate emotions, which affects their adjustment at school. A quantitative approach with a one-group pretest–posttest design was employed. The population included 329 eleventh-grade students at MA Negeri 2 Samarinda, with a purposive sample of six students identified as having low emotional intelligence. Data were collected using The Schutte Self-Report Emotional Intelligence Test (SSEIT) and analyzed through normality and paired sample t-tests. The average pretest score was 37.33, which increased to 71.00 after the group counseling intervention, showing an improvement of 33.67 points. These findings indicate that group counseling services significantly enhance emotional intelligence among eleventh-grade students, helping them better understand, manage, and express their emotions constructively.